GE_GERICHTE P/4234/2018 vom 8. August 2019 - GE Cour de justice (2019)
REFUS DE STATUER ; SOUPÇON ; ENQUÊTE PÉNALE ; CAS BÉNIN ; VIOLATION DE DOMICILE ; LÉSION CORPORELLE ; ASSISTANCE JUDICIAIRE | CPP.396.al2; CPP.310; cp.52; cp.123; cp.186; cpp.136